2011
DOI: 10.1038/nsmb.2045
|View full text |Cite
|
Sign up to set email alerts
|

The client protein p53 adopts a molten globule–like state in the presence of Hsp90

Abstract: It is not currently known in what state (folded, unfolded, alternatively folded) client proteins interact with chaperone Hsp90. We show that one client, the p53 DNA-binding domain, undergoes a structural change in the presence of Hsp90 to adopt a molten globule-like state. Addition of one- and two-domain constructs of Hsp90, as well as the full-length three-domain protein, to isotopically-labeled p53 results in reduction in NMR signal intensity throughout p53, particularly its central β-sheet. This reduction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
114
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 34 publications
7
114
1
Order By: Relevance
“…Subsequent studies by the Dyson group employed chemical shift perturbations and hydrogen/deuterium exchange to confirm that p53 core domain is in an unfolded dynamic ensemble [188]. Simultaneously, it was shown that the Hsp90 spectra only showed slight chemical shift changes giving rise to the conclusion that the interaction is highly dynamic [189], whereas another study using yeast Hsp90 by the Kessler group showed a direct interaction via a hydrophilic and salt-dependent patch in the C-terminal domain with a mainly folded p53 core domain [102].…”
Section: Hsp90mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies by the Dyson group employed chemical shift perturbations and hydrogen/deuterium exchange to confirm that p53 core domain is in an unfolded dynamic ensemble [188]. Simultaneously, it was shown that the Hsp90 spectra only showed slight chemical shift changes giving rise to the conclusion that the interaction is highly dynamic [189], whereas another study using yeast Hsp90 by the Kessler group showed a direct interaction via a hydrophilic and salt-dependent patch in the C-terminal domain with a mainly folded p53 core domain [102].…”
Section: Hsp90mentioning
confidence: 99%
“…Park et al investigated the complex between Hsp90 and the core domain of its substrate p53 [188,189], with the intriguing finding that p53 binds Hsp90 in a molten globule-like state [188].…”
Section: Chaperone-substrate Complexes Characterized By Nmr Spectroscopymentioning
confidence: 99%
“…Initially, it was originally hypothesised that any heat-mediated changes in keratinocyte biology would be induced by the heat shock response, an evolutionary conserved mechanism for cytoprotection against high temperatures (de Maio et al, 1996;King et al, 2001;Guo et al, 2007) (Chapter 2). Due to the effects of HSP72 and HSP90 on the JNK, p53 and PI3K/Akt pathways (Hagn et al, 2011;Park et al, 2011a;Walerych et al, 2010), an increase in the activity of these heat shock proteins is thought to mediate the protective effects of heat stress on epidermal cells.…”
Section: Uvb Plus Heat-induced Sirt1 Pathway In Keratinocytesmentioning
confidence: 99%
“…The whole scenario has become more complex by a recent nding that Hsp90 interacts with the p53 client, in that p53 is actually unfolded by Hsp90a, as judged by NMR spectroscopic measurements. 55 As a consequence p53 adopts a molten globule-like state. Thus, Hsp90 should not be solely regarded as a chaperone that simply helps transform its clients into a stable and xed tertiary structure.…”
mentioning
confidence: 99%